Studi Komparatif Efikasi Diri, Pendidikan Kewirausahaan Dan Minat Berwirausaha Mahasiswa Adbis Fisip Universitas 17 Agustus 1945 Surabaya Dengan Mahasiswa Adbis Fisip Universitas Hangtuah Surabaya - Afifa, Nia Dwi; Andayani, Sri; Pujianto, Agung (Research Journal of Social Science and Economics, 2025)
This research was conducted to find out whether there are differences in Self-Efficacy, Entrepreneurship Education and Interest in Entrepreneurship in Adbis faculty of social and political sciences Students at the University of 17 August 1945 Surabaya and Adbis faculty of social and political sciences Students at Hangtuah Surabaya. This type of research uses quantitative methods with comparative research types. This research was conducted by distributing questionnaires to selected respondents. The sampling technique used is probability sampling, which is carried out randomly using the random sampling technique, namely taking samples from the population at random. Then use the analysis of homogeneity test and different test t-test. The homogeneity test is used to determine the similarity or dissimilarity of the variants, while the t-test is different to determine whether there is an average difference between the two paired sample groups.